The Influence Of Work Discipline And Work Motivation On The Performance Of Employees At Bagja Nur Abadi Rajapolah Company, Tasikmalaya Regency - Dedi Mulyadi; Depy Muhamad Pauzy; Dudu Risana (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
This study aims to determine the simultaneous and partial effect of work discipline and work motivation on the performance of employees at bagja nur abadi Rajapolah company. The research method used is quantitative method with a survey approach. The sampling technique used a saturated sample with a total sample of 45 people. The data collection technique uses an offline questionnaire. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25. The results of the study show that work discipline and work motivation simultaneously have a significant effect on performance. Partially work discipline has a significant effect on performance. Partially, the work motivation has a significant effect on performance.